Adsorption of estrone with few-layered boron nitride nanosheets: Kinetics, thermodynamics and mechanism. (September 2018) - Liu, Guohong; Zhang, Zhaohan; Yan, Chen; Wang, Yang; Ma, Xuerui; Gao, Peng; Feng, Yujie
Abstract: Boron nitride Nanosheets (BNNSs) was fabricated with a method of heating the mixture of boric acid and urea in N2 atmosphere and used to remove estrone (E1 ) from water. The obtained BNNSs exhibited a higher surface area of 896 m 2 /g, a large pore volume of 0.76 cm 3 /g, and only few layers (0.398 nm) with the boric acid and urea ratio of 1:80. The layer number of BNNSs decreased from 15 to 4 with the mole ratio of boric acid and urea decreasing from 1:20 to 1:80, which was identified by SEM, TEM, AFM and BET measurements. More importantly, BNNSs presented an outstanding adsorption performance for estrone with the adsorption capacity of 249.15 mg E1 /g BNNSs. The adsorption process could be best fitted by pseudo second-order kinetic model and the equilibrium data at different temperatures were well fitted by Langmuir isotherm model. The thermodynamics analysis revealed that E1 adsorption on BNNSs was spontaneous (ΔG = −29.33 kJ mol −1 ), enthalpy-retarded (ΔH = 29.75 kJ mol −1 ), entropy-driven (ΔS = 198.26 J mol −1 K −1 ), and mostly chemical adsorption. The adsorption rates of E1 in water were sharply enhanced with thinner BNNSs as absorbents and removal efficiency by BN-60 regenerated after 6 times was above 95%, it was shown that the surface areas, mesopores and remarkable structure played important roles in the adsorption process. The firmness of E1 onto BNNSs and the stability of adsorption efficiency made BNNSs as a potential absorbent for efficient removal of E1 from wastewater. Graphical abstract: Few layers BNNSs with large surface area and massive mesopores could provide more active sites for E1 adsorption and the adsorption process was owing to π-π interaction, hydrophobic effects and Van der Waals' force. Image 1 Highlights: Porous and fewer layer BNNSs were prepared with the ratio regulation of urea and boric acid. The E1 adsorption capacity could reach to 249.15 mg E1 /g with thinner BNNSs. E1 adsorption on BNNSs was spontaneous, enthalpy-retarded, entropy-driven, and mostly chemical adsorption. The removal efficiency of E1 by BN-60 regenerated after 6 times was above 95%.